Technical Efficiency Analysis of Rice Farming in Deli Serdang Regency: A Data Envelopment Analysis (DEA) Approach - Angin, Chornelius Perangin; Pakpahan, Helena Tatcher; Nababan, Manaor Bismar Posman (University of Jember, 2023)
Deli Serdang Regency is the leading rice producer in North Sumatra Province. The fact is that productivity in Deli Serdang Regency has stagnated. The problem experienced by farmers is that farmers still apply monoculture cropping patterns, namely farming with only one type of crop each year, climate change, and rising input prices. This study aims to determine whether rice farming is run by farmers in Deli Serdang Regency, whether or not it is efficient, and to find out the socio-economic factors that influence technical efficiency in Deli Serdang Regency. Our study uses the Data Envelopments Analysis (DEA) method and Tobit regression to measure the technical efficiency of 400 rice farmers. Our study found that the value of technical efficiency based on the CRS, VRS, and SE assumptions was 0.576, 0.806, and 0.717. These three values mean that inefficient rice farming must reduce inputs by 42.6%, 19.4%, and 28.3%, respectively, so inefficient farming becomes efficient. Our study also found that factors that increase technical efficiency are education, access to credit, access to irrigation, distance to markets, experience, and crop diversification. Factors reducing technical efficiency are climate change and rising input prices.